Landscape metrics application in ecological and visual landscape assessment - Gavrilović Suzana (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2017)
The development of landscape-ecological approach application in spatial planning provides exact theoretical and empirical evidence for monitoring ecological consequences of natural and/or anthropogenic factors, particularly changes in spatial structures caused by them. Landscape pattern which feature diverse landscape values is the holder of the unique landscape character at different spatial levels and represents a perceptual domain for its users. Using the landscape metrics, the parameters of landscape composition and configuration are mathematical algorithms that quantify the specific spatial characteristics used for interpretation of landscape features and processes (physical and ecological aspect), as well as forms (visual aspect) and the meaning (cognitive aspect) of the landscape. Landscape metrics has been applied mostly in the ecological and biodiversity assessments as well as in the determination of the level of structural change of landscape, but more and more applied in the assessment of the visual character of the landscape. Based on a review of relevant literature, the aim of this work is to show the main trends of landscape metrics within the aspect of ecological and visual assessments. The research methodology is based on the analysis, classification and systematization of the research studies published from 2000 to 2016, where the landscape metrics is applied: (1) the analysis of landscape pattern and its changes, (2) the analysis of biodiversity and habitat function and (3) a visual landscape assessment. By selecting representative metric parameters for the landscape composition and configuration, for each category is formed the basis for further landscape metrics research and application for the integrated ecological and visual assessment of the landscape values. Contemporary conceptualization of the landscape is seen holistically, and the future research should be directed towards the development of integrated landscape assessment as a guideline for spatial development planning.